2020
DOI: 10.1159/000505323
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rectal Cancer-Induced Disseminated Carcinomatosis of the Bone Marrow with FOLFOX plus Cetuximab and Panitumumab

Abstract: Keywords Disseminated carcinomatosis of the bone marrow · Cetuximab · Colorectal cancer · PanitumumabAbstract Disseminated carcinomatosis of the bone marrow (DCBM) in colorectal cancer is an extremely rare complication with a poor prognosis. Here, we report a case of DCBM due to rectal cancer successfully treated with a combination of FOLFOX and an anti-epidermal growth factor receptor (EGFR) agent. The patient was a 38-year-old man diagnosed with rectal cancer with multiple bone and para-aortic lymph node met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Subsequently, systemic chemotherapy should be initiated if possible, in order to control the metastatic disease which is the underlying cause of the haematological disorder. There have been case reports of successful treatment with XELOX and FOLFOX based regime with bevacizumab or cetuximab as adjuvant therapy 4,5,8–11,13,14,16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, systemic chemotherapy should be initiated if possible, in order to control the metastatic disease which is the underlying cause of the haematological disorder. There have been case reports of successful treatment with XELOX and FOLFOX based regime with bevacizumab or cetuximab as adjuvant therapy 4,5,8–11,13,14,16 …”
Section: Discussionmentioning
confidence: 99%
“…There have been case reports of successful treatment with XELOX and FOLFOX based regime with bevacizumab or cetuximab as adjuvant therapy. 4,5,[8][9][10][11]13,14,16 In the subset of patients who may be too frail or otherwise deemed unsuitable for chemotherapy, palliation would be the best course of action. Goals of care should be discussed early in this aggressive disease and symptomatic medications including opioids should be administered early and titrated to the patient's symptoms.…”
Section: Prognosis and Consideration Of Systemic Chemotherapymentioning
confidence: 99%
“…Recently, the successful treatment of DCBM from various malignancies has been reported. In the past 3 years, two English‐language papers have reported that anticoagulation and chemotherapy for DCBM from gastrointestinal adenocarcinoma have led to the discharge of patients from the hospitals 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…In the past 3 years, two English-language papers have reported that anticoagulation and chemotherapy for DCBM from gastrointestinal adenocarcinoma have led to the discharge of patients from the hospitals. 21,22 Disseminated carcinomatosis of the bone marrow is associated with a high rate of DIC, and its prognosis is very poor. Aggressive treatment of malignancy improves DCBM prognosis.…”
Section: Discussionmentioning
confidence: 99%